Continuous glucose monitoring can disclose glucose fluctuation in advanced Parkinsonian syndromes - Hiroyuki Todo (MDPI AG, 2018)
Continuous glucose monitoring (CGM) is a method to examine glucose concentration in subcutaneous interstitial fluid sequentially. CGM can disclose glucose fluctuation (GF), which can be unrecognized in routine blood tests. A limited number of studies suggest advanced Parkinsonian syndromes (PS) is at risk of GF, however, the report of CGM in PS is scarce. We performed CGM for 72 h in 11 nondiabetic patients with advanced PS. The etiology was Parkinson's disease, multiple system atrophy, progressive supranuclear palsy, or dementia with Lewy bodies. All participants were bedridden, elderly (≥65 year-old), and receiving enteral nutrition. The retrospective data was obtained after the removal of CGM device. In the glucose concentration, 9 (81.8%) participants showed nocturnal decline (≤70 mg/dL; 4 of them reached recordable limit of 40 mg/dL), and 6 (54.5%) participants showed remarkable elevation (≥200 mg/dL) postprandially. In the majority, these abnormalities were difficult to predict from routine blood tests. Standard deviation and mean of sequential glucose concentration were higher than those in precedent reports of young or middle-aged healthy controls. CGM in nondiabetic and elderly patients with advanced PS can disclose GF, with features of nocturnal decline and/or postprandial remarkable elevation of glucose concentration. Owing to limitations such as small sample size, heterogeneity of etiology, and retrospectivity of CGM data, further investigations are required.